Sezonowe wahania sprzedaży i zakupu miodu w przedsiębiorstwie przetwórczym - Śrubkowska, Małgorzata; Pawłowska-Tyszko, Joanna (Seasonal Fluctuation of Sale and Purchase of Honey in Food-Processing Company, 2006)
The work's aim is to show the seasonal fluctuation of sale and purchase of honey in a food-processing company. In the article to analyse the empirical material and calculations of seasonal fluctuation in sale and purchase, the authors use the method of trend's function, that is the method of coefficients. The audit and observations of demand size for honey show, that it decreases in the period of the largest gatherings and increases in winter, which is connected with specific proprieties of this product.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 429-437